(الوساطة المالية في المصارف الإسلامية (دراسة تطبيقية على بنت التمويل الكويتي في ماليزيا - Khaled Mohamad Abdullah (Universiti Sains Islam Malaysia, 2024)
Thesis (M.A)-- Faculty of Shariah and Law, Universiti Sains Islam Malaysia, 2013